Flux paste suitable for high-precision brazing

By using specific composition flux, paste and dispersant in the brazing paste, and performing refinement, grinding and emulsification, the problem of existing brazing paste forming residual carbon and fine needle tube blockage at high temperature is solved, and the stable and efficient welding effect of high-precision brazing is achieved.

CN119681496APending Publication Date: 2025-03-25HANGZHOU HUAGUANG ADVANCED WELDING MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411952802.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Existing brazing paste is prone to form residual carbon at high temperatures, resulting in deterioration of welding effect, and is prone to clogging the needle tube in automated dispensing applications of fine needle tubes, which cannot effectively solve the problems of layering and stability.

Method used

The combination of flux, paste forming and dispersant is designed, where the flux consists of boric acid, potassium fluoroborate, potassium fluoride, cadmium fluoride, lithium chloride. The paste forming uses polymers and organic solvents, and the dispersant uses cetyl polyoxyethylene ether, etc., through refining, grinding and emulsifying treatment, the fineness and moisture content of the particulate matter meet the requirements.

Benefits of technology

It effectively solves the problems of layering, residual carbon and fine needle blockage, greatly improves the technical effect of high-precision brazing, ensures no carbon residue after welding, and improves the storage stability of solder paste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to paste flux suitable for high-precision brazing, which is composed of the following components in parts by weight: 65 to 70 parts of brazing flux, 30 to 35 parts of paste forming body, and 0.1 to 1 part of dispersing agent. The brazing flux is composed of boric acid, potassium fluoborate, potassium fluoride, cadmium fluoride and lithium chloride, the boric acid accounts for 40%-60% of the total mass of the brazing flux, and the potassium fluoborate accounts for 15%-35% of the total mass of the brazing flux; the potassium fluoride accounts for 10%-40% of the total mass of the soldering flux, the cadmium fluoride accounts for 5%-30% of the total mass of the soldering flux, the lithium chloride accounts for 5%-20% of the total mass of the soldering flux, the paste forming body adopts a polymer and an organic solvent, and the dispersing agent adopts a solvent beneficial to preventing the soldering flux, the paste forming body and the dispersing agent from forming polymeric particles after being mixed. The problem of layering, the problem of carbon residue and the problem of needle tube blockage caused by dispensing of a thin needle tube are solved at the same time, and the high-precision brazing effect is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a flux paste suitable for high-precision brazing and a preparation method thereof, and is mainly suitable for brazing between stainless steel and cemented carbide materials. Background Art

[0002] See the reference document with publication number CN106514044A and patent application name “Copper-based solder paste”. The solder paste is a mixture of alcohol organic solvent, silicone oil or caprylic acid glyceride and ammonium triacetate as a paste, but the paste viscosity is too low to effectively inhibit the stratification of the solder and the solder. In the Chinese invention document with publication number CN1586795A and invention name “A copper solder paste for automatic soldering and its preparation method”, fatty acid glyceride is used as a surfactant in the solder paste to ensure the compatibility of the inorganic solder and the paste, and benzotriazole, unsaturated fatty acid ester and animal and vegetable oil are added as additives to further improve the anti-stratification stability of the solder paste. In the actual soldering process, fatty acid glyceride, animal and vegetable oil and unsaturated fatty acid ester are very easy to form residual carbon under the combined action of high temperature and solder, which deteriorates the welding effect. In addition, when using a fine needle tube for automatic dispensing, the solder paste of the prior art will have the problem of clogging the needle tube. Summary of the invention

[0003] The technical problem solved by the present application is to overcome the above-mentioned deficiencies existing in the prior art and to provide a flux paste suitable for high-precision brazing and a preparation method thereof.

[0004] The technical solution adopted by the present application to solve the above technical problems includes: a flux paste suitable for high-precision brazing, the flux paste is composed of a brazing agent, a paste and a dispersant, and its components (by mass) are: 65-70 parts of brazing agent, 30-35 parts of paste, and 0.1-1 part of dispersant; the brazing agent is composed of boric acid, potassium fluoroborate, potassium fluoride, cadmium fluoride, and lithium chloride, the boric acid accounts for 40%-60% of the total mass of the brazing agent, and the potassium fluoroborate accounts for 15%-35% of the total mass of the brazing agent; the potassium fluoride accounts for 10%-40% of the total mass of the brazing agent, the cadmium fluoride accounts for 5%-30% of the total mass of the brazing agent, and the lithium chloride accounts for 5%-20% of the total mass of the brazing agent, the paste uses a polymer and an organic solvent, and the dispersant uses a solvent that helps prevent the formation of polymerized (larger) particles after the brazing agent, the paste and the dispersant are mixed. The present application achieves the goal of simultaneously solving the stratification problem, the carbon residue problem, and the problem of needle tube clogging caused by fine needle dispensing through the coordinated design of flux, paste, and dispersant, thereby greatly improving the technical effect of high-precision brazing.

[0005] The particle fineness of the solder paste is ≤30um, ensuring that the dispensing needle is 24G and the automatic dispensing will not be blocked when the inner diameter of the dispensing needle is 0.31mm.

[0006] The water content of the soldering paste in this application is ≤2%, ensuring that when the soldering paste in this application is heated from room temperature to above 800°C within 2-3s, no splashing will be generated due to water vapor explosion.

[0007] The polymer accounts for 10%-20% of the mass of the paste, and the organic solvent accounts for 80%-90% of the mass of the paste.

[0008] Furthermore, the dispersant is at least one of cetyl alcohol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, and oleic acid.

[0009] Furthermore, the polymer is at least one of polyisobutylene with a viscosity average molecular weight of 800,000, polyisobutylene with a viscosity average molecular weight of 1,110,000, SEEPS produced by KURARAY, SEBS produced by KURARAY, SEPS produced by KURARAY and other butyl rubbers with a molecular weight greater than 800,000. When the processing temperature of the above polymer is higher than 300°C, it can be rapidly cracked into polymer monomer small molecules or fragments composed of several monomer small molecules, and rapidly vaporize and detach at high temperature, so there is no carbon residue under the action of high temperature.

[0010] Furthermore, the organic solvent is an alkane mixture.

[0011] The technical solution adopted by the present application to solve the above technical problems also includes a method for preparing the above soldering paste. The method is characterized in that it comprises the following steps: S1: drying the brazing flux powder and putting it into a crusher to refine the powder, and sieving the obtained powder through a 400-mesh sieve to obtain a mixed and refined brazing flux powder; S2: adding the polymer to an organic solvent, heating to 80-130°C, and stirring thoroughly to form a uniform and stable solution; S3: adding the mixed and refined flux powder obtained in step S1 to the paste obtained in step S2, and adding a dispersant, stirring and mixing at a speed of 25-70 rpm to obtain a mixed flux paste; S4 grinds the mixed solder paste with a grinding interval of 10-70 microns to remove large particles to obtain refined solder paste; S5 emulsifies the refined solder paste for 15-60 minutes to obtain a finished solder paste that is evenly mixed and refined again.

[0012] Compared with the prior art, the present application has the following advantages and effects: it simultaneously solves the stratification problem, the carbon residue problem, and the problem of needle tube clogging caused by fine needle dispensing, and greatly improves the high-precision brazing effect. DETAILED DESCRIPTION

[0013] The present application includes a soldering paste suitable for high-precision soldering, wherein the soldering paste is composed of a soldering agent, a paste body and a dispersant, and the components are: 65-70 parts of the soldering agent, 30-35 parts of the paste body and 0.1-1 part of the dispersant.

[0014] The brazing agent comprises: boric acid, potassium fluoroborate, potassium fluoride, cadmium fluoride and lithium chloride. The boric acid accounts for 40%-60% of the total mass of the brazing agent, the potassium fluoroborate accounts for 15%-35% of the total mass of the brazing agent; the potassium fluoride accounts for 10%-40% of the total mass of the brazing agent, the cadmium fluoride accounts for 5%-30% of the total mass of the brazing agent, and the lithium chloride accounts for 5%-20% of the total mass of the brazing agent.

[0015] The paste comprises: a polymer and an organic solvent, wherein the polymer accounts for 10%-20% of the mass of the paste, and the organic solvent accounts for 80%-90% of the mass of the paste.

[0016] Furthermore, the dispersant is at least one of cetyl alcohol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, and oleic acid; Furthermore, the polymer is at least one of polyisobutylene with a viscosity average molecular weight of 800,000, polyisobutylene with a viscosity average molecular weight of 1,110,000, SEEPS produced by KURARAY, SEBS produced by KURARAY, SEPS produced by KURARAY and other butyl rubbers with a molecular weight greater than 800,000. The above polymers can be rapidly cracked into polymer monomer small molecules or fragments composed of several monomer small molecules at high temperature, and rapidly vaporize and detach at high temperature, so that no carbon residue is left under the action of high temperature.

[0017] Furthermore, the organic solvent is an alkane mixture.

[0018] The particle size of this application is ≤30um, suitable for precision dispensing; The water content is ≤2%, which reduces the instability caused by water absorption; Solid content ≥65%.

[0019] The following embodiments are specific applications of the present application, but the present application is not limited to the following embodiments.

[0020] Embodiment 1: This embodiment provides a high-precision soldering flux paste, which is composed of a flux, a paste, and a dispersant in a mass ratio of 65:34:1, wherein: The flux composition is composed of the following: boric acid accounts for 40% of the total mass of the flux, potassium fluoroborate accounts for 15% of the total mass of the flux, potassium fluoride accounts for 20% of the total mass of the flux, the cadmium fluoride accounts for 10% of the total mass of the flux, and the lithium chloride accounts for 10% of the total mass of the flux; The paste composition is composed of the following: polymer accounts for 13% of the paste mass, and organic solvent accounts for 87% of the paste mass.

[0021] In this embodiment, the dispersant is fatty alcohol polyoxyethylene ether.

[0022] In this embodiment, the polymer is polyisobutylene with a viscosity average molecular weight of 800,000.

[0023] In this embodiment, the organic solvent is a saturated hydrocarbon mixture with a distillation range of 204°C-243°C.

[0024] The preparation method of the soldering paste comprises the following steps in sequence: The first step is to mix and refine the flux; The brazing flux powder is dried and then put into a crusher to be finely ground. The obtained powder is sieved through a 400-mesh screen to obtain a mixed and fined brazing flux powder (the water content of the brazing flux powder is measured to be less than 1%). Step 2: Preparation of paste Add the polymer to the organic solvent, heat to 100°C, and stir thoroughly to form a uniform and stable solution; Step 3: Mixing and homogenizing the flux and paste The mixed and refined flux powder obtained in the first step is added to the paste obtained in the second step, and a dispersant is added and stirred at a speed of 30 rpm to obtain a mixed flux paste; Grinding the mixed solder paste with a grinding interval of 50 microns to remove large particles and obtain refined solder paste; The refined solder paste is emulsified for 30 minutes to obtain a finished solder paste that is evenly mixed and refined again (the emulsification process is a process of high-speed shearing, dispersion, and collision, which makes the particles in the solder paste smaller and more uniform); After high-frequency induction welding, the obtained solder paste has no carbon residue after welding, and can ensure a stable storage period of 6 months, and the solder paste will not be stratified during the storage period.

[0025] Embodiment 2: This embodiment provides a high-precision soldering flux paste, which is composed of a flux, a paste, and a dispersant in a mass ratio of 68:31.25:0.75, wherein: The flux composition is composed of the following: boric acid accounts for 50% of the total mass of the flux, potassium fluoroborate accounts for 30% of the total mass of the flux, potassium fluoride accounts for 10% of the total mass of the flux, the cadmium fluoride accounts for 5% of the total mass of the flux, and the lithium chloride accounts for 5% of the total mass of the flux; The paste composition is composed of the following: polymer accounts for 15% of the paste mass, and organic solvent accounts for 85% of the paste mass.

[0026] In this embodiment, the dispersant is oleic acid.

[0027] In this embodiment, the carbon-free polymer is butyl rubber with a molecular weight greater than 800,000.

[0028] In this embodiment, the organic solvent is a saturated hydrocarbon mixture with a distillation range of 204°C-243°C.

[0029] The preparation method of the soldering paste comprises the following steps in sequence: The first step is to mix and refine the flux; The brazing flux powder is dried and then put into a crusher to be finely ground. The obtained powder is sieved through a 400-mesh screen to obtain a mixed and fined brazing flux powder (the water content of the brazing flux powder is measured to be less than 1%). Step 2: Preparation of paste Add the polymer to the organic solvent, heat to 120°C, and stir thoroughly to form a uniform and stable solution; Step 3: Mixing and homogenizing the flux and paste The mixed and refined flux powder obtained in the first step is added to the paste obtained in the second step, and a dispersant is added and stirred at a speed of 30 rpm to obtain a mixed flux paste; Grind the mixed solder paste with a grinding interval of 30 microns to remove large particles and obtain refined solder paste; The refined solder paste is emulsified for 45 minutes to obtain a finished solder paste that is evenly mixed and refined again. After high-frequency induction welding, the obtained solder paste has no carbon residue after welding, and can ensure a stable storage period of 8 months, and the solder paste will not be stratified during the storage period.

[0030] The technical features of this application include: 1) The material is small in fineness, and the needle will not be blocked when using a fine needle for automated dispensing (the dispensing needle can be 24G, with an inner diameter of 0.31mm), which can meet the needs of automated dispensing for precision brazing applications; 2) The material uses a high-boiling point non-aqueous system with a low water content. It can be heated to above 800°C in a very short time (2-3s) without splashing due to water vapor explosion; 3) The flux is usually composed of inorganic salts and has a certain solubility in water. The water content in the material is low, which increases the storage stability of the flux.

[0031] In the prior art, there is no corresponding control over the fineness and water content of the solder paste. The fineness test can easily identify the discrete solid particles in the solder paste and select a needle with a suitable aperture for precise dispensing without clogging. Failure to control the water content will result in high-temperature splashing during rapid heating.

[0032] Comparative Example: The soldering paste of the comparative example of the present application is composed of a flux and a paste in a mass ratio of 65:34:1, and no dispersant is added.

[0033] in: The flux composition is composed of the following: boric acid accounts for 45% of the total mass of the flux, potassium fluoroborate accounts for 15% of the total mass of the flux, potassium fluoride accounts for 20% of the total mass of the flux, the cadmium fluoride accounts for 10% of the total mass of the flux, and the lithium chloride accounts for 10% of the total mass of the flux; The paste composition is composed of the following: polymer accounts for 13% of the paste mass, and organic solvent accounts for 87% of the paste mass.

[0034] The carbon-free polymer is polyisobutylene with a viscosity average molecular weight of 800,000.

[0035] The organic solvent is a saturated hydrocarbon mixture with a distillation range of 204°C-243°C.

[0036] The preparation method of the comparative example solder paste comprises the following steps in sequence: The first step is to mix and refine the flux; The brazing flux powder is dried and then put into a crusher to be finely ground. The obtained powder is sieved through a 400-mesh screen to obtain a mixed and fined flux powder (the moisture content of the flux powder is measured to be less than 1%). Step 2: Preparation of paste Add the polymer to the organic solvent, heat to 100°C, and stir thoroughly to form a uniform and stable solution; Step 3: Mixing and homogenizing the flux and paste The mixed and refined flux powder obtained in the first step is added to the paste obtained in the second step, and the mixture is stirred and mixed at a speed of 30 rpm to obtain a mixed flux paste; Grinding the mixed solder paste with a grinding interval of 50 microns to remove large particles and obtain refined solder paste; The refined solder paste is emulsified for 30 minutes to obtain a finished solder paste that is evenly mixed and refined again. Dispersants can increase the compatibility and stability between flux powder and paste. If no dispersant is added and the two are simply mixed together by stirring, they are very likely to separate. This is because the flux powder has a strong polarity, while the paste has a weak polarity, and the compatibility between the two is not high, so separation will occur. At the same time, the pinholes will be blocked during the dispensing process, which is not conducive to the storage stability and precision operation of the solder paste.

Claims

1. A flux paste suitable for high-precision brazing, characterized by: The soldering solder paste is composed of a brazing agent, a paste and a dispersant, and the components are: 65-70 parts of the brazing agent, 30-35 parts of the paste and 0.1-1 part of the dispersant; the brazing agent is composed of boric acid, potassium fluoroborate, potassium fluoride, cadmium fluoride and lithium chloride, the boric acid accounts for 40%-60% of the total mass of the brazing agent, the potassium fluoroborate accounts for 15%-35% of the total mass of the brazing agent; the potassium fluoride accounts for 10%-40% of the total mass of the brazing agent, the cadmium fluoride accounts for 5%-30% of the total mass of the brazing agent, and the lithium chloride accounts for 5%-20% of the total mass of the brazing agent; the paste adopts a polymer and an organic solvent, and the dispersant adopts a solvent that helps to prevent the brazing agent, the paste and the dispersant from forming polymer particles after mixing.

2. The soldering paste suitable for high-precision soldering according to claim 1, characterized in that: The particle size of solder paste is ≤30um.

3. The soldering paste suitable for high-precision soldering according to claim 1, characterized in that: The moisture content of solder paste is ≤2%.

4. The soldering paste suitable for high-precision soldering according to claim 1, characterized in that: The polymer accounts for 10%-20% of the paste mass, the organic solvent accounts for 80%-90% of the paste mass, and the polymer is cracked into polymer monomer small molecules or fragments thereof and gasified at a temperature above 300°C.

5. The soldering paste suitable for high-precision soldering according to claim 1, characterized in that: The dispersant is at least one of cetyl alcohol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, and oleic acid.

6. The soldering paste suitable for high-precision soldering according to claim 4, characterized in that: The polymer is at least one of polyisobutylene with a viscosity average molecular weight of 800,000, polyisobutylene with a viscosity average molecular weight of 1,110,000, SEEPS produced by KURARAY, SEBS produced by KURARAY, SEPS produced by KURARAY and other butyl rubbers with a molecular weight greater than 800,000.

7. The soldering paste suitable for high-precision soldering according to claim 4, characterized in that: The organic solvent is an alkane mixture with a distillation range of 204°C-243°C.

8. The method for preparing the soldering paste according to any one of claims 1 to 7, characterized in that The following steps are involved: S1: drying the flux powder and putting it into a crusher to refine the powder, and sieving the obtained powder through a 400-mesh sieve to obtain a mixed and refined flux powder; S2: adding the polymer to an organic solvent, heating to 80-130°C, and stirring thoroughly to form a uniform and stable solution; S3: adding the mixed and refined flux powder obtained in step S1 to the paste obtained in step S2, and adding a dispersant, stirring and mixing at a speed of 25-70 rpm to obtain a mixed flux paste; S4 grinds the mixed solder paste with a grinding interval of 10-70 microns to remove large particles to obtain refined solder paste; S5 emulsifies the refined solder paste for 15-60 minutes to obtain a finished solder paste that is evenly mixed and refined again.

Citation Information

Patent Citations

  • Copper-based brazing paste

    CN106514044A